A Midsummer Night's Play Based on a Play by Adam Oehlenschläger - Oehlenschläger, Adam (The Jørgen Leth Collection - Fiction Films, 2008)
"A Midsummer Night's Play" is an 1803 Danish Golden-Age classic by the Romantic poet Adam Oehlenschläger. Paying tribute to poetry, the production is faithful to the original text. Leth and Kirkeby present the play in tableau form, featuring the finest Danish actors of the day in a festive romp through Oehlenschläger's elaborate verse and metrics. [www.dfi.dk]